A Randomized Controlled Trial Comparing the Physical Performance of Soccer Players With and Without Anterior Cruciate Ligament Reconstruction While Undergoing Knee Injury Prevention Training - Amir Shamlou kazemi; hassan daneshmandi; Parisa Sedaghti; Yasin Hoseini (Journal of Rehabilitation Sciences and Research)
Background: Anterior cruciate ligament (ACL) rupture is one of the most severe and complex knee injuries commonly occurring in soccer. The Sportsmetrics Soccer Training (SMST) protocol is a well-established program for preventing knee injuries and enhancing soccer players' performance. This study aimed to compare the effect of the SMST injury prevention protocol on the performance of soccer players with and without anterior cruciate ligament reconstruction (ACLR). Methods: This research employed a semi-experimental design, including 42 soccer players aged 18–30, each with at least three years of regular soccer experience. Participants were divided into two groups of 21 subjects: players with ACLR and those without ACLR. Physical performance was evaluated using the Illinois Agility Test, 40-Yard Sprint Test, and Sargent Vertical Jump Test in both groups before and after six weeks of intervention. The SMST protocol was conducted in three 90-minute weekly sessions for six weeks. Statistical analyses were performed to assess intra-group differences using the dependent t-test and inter-group differences using the covariance analysis test (P ≤ 0.05). Results: The dependent t-test results demonstrated significant improvements in speed (P = 0.01), agility (P = 0.01), and explosive power (P = 0.01) in both groups following six weeks of SMST training. However, the results of the covariance analysis revealed no significant differences between the two groups in terms of speed (P = 0.57), agility (P = 0.07), and explosive power (P = 0.71) after six weeks of training. Conclusion: The improvements in performance indicators among the participants were primarily attributed to the alignment between the components of the SMST protocol and the performance evaluation tests. SMST training is highly recommended for healthy and ACLR soccer players, as it effectively enhances physical and athletic performance while reducing the risk of ACL injury and re-injury.